2006
DOI: 10.1111/j.1532-849x.2006.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Repair Methods for Ceramic‐Fused‐to‐Metal Crowns

Abstract: The conditioning methods (Groups 1 to 3) of the repair surfaces did not show differences between each other; each resulted in mean fracture loads at lower levels than that of the intact crowns. Addition of an FRC layer increased the fracture load to the level of intact crowns. This suggests that the use of FRC in repairs of metal-ceramic crowns might be a viable option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
(23 reference statements)
1
36
0
1
Order By: Relevance
“…On this ground, thermocycling before fracture load testing was used as an aging method in this study. Previous research on veneer repairs has shown the beneficial effects of bidirectional FRC on interfacial strength and crack propagation [20][21][22] . The addition of fibers close to the preparation surface was expected to reinforce the weakened tooth structure and distribute stresses evenly, to the end of avoiding detrimental stress concentrations at the cervical and incisal sites 33) of the laminate veneer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this ground, thermocycling before fracture load testing was used as an aging method in this study. Previous research on veneer repairs has shown the beneficial effects of bidirectional FRC on interfacial strength and crack propagation [20][21][22] . The addition of fibers close to the preparation surface was expected to reinforce the weakened tooth structure and distribute stresses evenly, to the end of avoiding detrimental stress concentrations at the cervical and incisal sites 33) of the laminate veneer.…”
Section: Discussionmentioning
confidence: 99%
“…The further impregnation of the polymer-preimpregnated fibers with a light-curing resin matrix formed a semiinterpenetrating polymer network of relatively coarse structure. This structure was previously shown to boost the bonding strength 19,22) . After further impregnation, the FRC layer was applied to the prepared tooth surface.…”
Section: Cementationmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura também relata a utilização de métodos tais como jateamento com partículas de óxido de alumínio-Al 2 O 3 (SHAHVERDI et al, 1998;WOLF et al, 1992;KIM et al, 2005;YESIL et al, 2007), asperização com pontas diamantadas (Kupiec et al, 1996), aplicação de silano (AGRA et al, 1993, DELLA BONA;NORTHEAST, 1994) e deposição de uma camada de sílica (SiOx) (OZCAN et al, 2006) sobre a cerâmica fraturada.…”
Section: Discussionunclassified
“…On the repair of fractured porcelain veneers with resin composites, higher fracture loads were reported when a layer of glass fiber weave was placed between the crown and the repair resin composite 24,25) . In particular, in the study by Vallittu 24) , a fiber weave layer was expanded over the incisal edge of the crown, thus providing a reinforced mechanical interlocking of the resin composite to the metal crown.…”
Section: Introductionmentioning
confidence: 99%